2018
DOI: 10.2214/ajr.17.17923
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Postsurgical Imaging Surveillance of Breast Cancer Patients: A Nationwide Survey Study

Abstract: The optimal surveillance mammography regimen must be better defined. This preliminary study showed variability in diagnostic versus screening surveillance mammography for women with a history of breast cancer. Future studies should evaluate why these variations occur and how to standardize recommendations to tailor personalized imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In 2018, findings from a national 8-question online survey of radiologists regarding their use of diagnostic versus screening mammography for women with a PHBC found significant variability in imaging protocols for women with a PHBC based on women's treatment (lumpectomy versus mastectomy) and facility characteristics. 31 Radiologists reported that protocols for women with lumpectomy were more likely to have a combination of diagnostic and screening examinations compared to women with mastectomy, who were more likely to have diagnostic only or screening only examinations. The most frequently reported imaging interval was every 6 months for 1-2 years (49%), with the next most common interval every 12 months for 2-5 years then screening (33%), and the least common interval was for 6 months-1 year then screening (18%).…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, findings from a national 8-question online survey of radiologists regarding their use of diagnostic versus screening mammography for women with a PHBC found significant variability in imaging protocols for women with a PHBC based on women's treatment (lumpectomy versus mastectomy) and facility characteristics. 31 Radiologists reported that protocols for women with lumpectomy were more likely to have a combination of diagnostic and screening examinations compared to women with mastectomy, who were more likely to have diagnostic only or screening only examinations. The most frequently reported imaging interval was every 6 months for 1-2 years (49%), with the next most common interval every 12 months for 2-5 years then screening (33%), and the least common interval was for 6 months-1 year then screening (18%).…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to evaluate reasons behind facility coding patterns, which are likely multifactorial. Ordering provider practices may ultimately be determining indication coding; however, the BCSC does not have ordering provider information and ultimately facilities may recode examinations based on standardized coding practices [25]. We were also unable to evaluate the potential influence of factors such as geography that ties to urbanicity and access, which may be important factors driving practice variability.…”
Section: Limitationsmentioning
confidence: 99%
“…The mortality of breast cancer recurrence potentially can be reduced from 47% to 20% with annual mammographic surveillance [2]. A prior study in 2015 found a general variability in surveillance imaging protocols after breast-conserving surgery in practices across the United States, with the majority of surveyed practices recommending annual diagnostic mammography (DM) between 2 and 5 years before returning to annual screening mammography (SM) [3]. In 2019, the ACR updated its Appropriateness Criteria for surveillance of asymptomatic stage 1 breast cancer to the use of either SM or DM for imaging surveillance after breast-conserving surgery without an established time frame if DM is used [4].…”
mentioning
confidence: 99%
“…Currently, after breast-conserving surgery, there is little to no evidencebased literature to determine which type of mammography, screening or diagnostic, is superior for surveillance imaging or the optimal duration of DM follow-up before returning to annual SM [3]. Furthermore, the lack of consistent recommendations from the NCCN and ACR for surveillance imaging after breast-conserving surgery has resulted in immense variability in clinical practice.…”
mentioning
confidence: 99%
See 1 more Smart Citation